Jira 8 essentials : a practical Jira 8 guide for effective project tracking and issue management that explores the enhanced Jira features /: a practical Jira 8 guide for effective project tracking and issue management that explores the enhanced Jira features. (2022) - Li, Patrick, 1983-
No abstract available